THE DRAMATURGY OF THE AMBITION TO ELIMINATE CORRUPTION : THE BRIBERY CASE OF IMPORTED SUGAR DISTRIBUTION - Teddy Asmara; Abdul Wahid (Universitas Muhammadiyah Ponorogo, 2019)
This non-doctrinal study analyzes the practice of ignoring the values of logical-factual justice and righteousness to eliminate corruption among the high-positioned state officials. The aim is to describe the establishment of criminal trials which are ambitious, which yet has counterproductive effects. There is not only injustice, but there is also the ignorance of the premise of material righteousness as the rational working character of criminal law. The primary data is in the form of interview to the perpetrators and the informants. The secondary data is in the form of case documents, which are analyzed qualitatively with the hermeneutic interpretation technique. Results of the study show that the ambitious elimination of corruption has the potentials to break the logics of criminal trials and restricts the ratio and conscience of law enforcers.